Observations on the Mechanisms of the Thermal and Photoinduced Oxidation of D-Mannitol and Fucoidan by Transition Metal Complexes and Inorganic Radicals - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Chandia-Parra, N (2011)
The mechanism of the D-mannitol and fucoidan oxidation by ?OH, peroxyl radicals, PRX? = O ?-2, HOCH2O?2, and CH2(O?2)CO-2, inorganic radicals, NO?3, Cl?- 2, and [NiIII(Me6-[14]aneN4)H 2O]3+ was investigated by pulse radiolysis. Relative to the diffusion-controlled reaction of the ?OH radical, the reactions of PRX?, NO?3, and Cl ?-2 are slow, with a 105-106 (mol L-1)-1 s-1 order of magnitude. The formation of saccharide-Ni(III) complexes also accounts for oxidation of the D-mannitol and fucoidan by [NiIII (Me6-[14]aneN 4)H2O] 3+. A rate constant k = 2.2 × 107 (mol L-1)-1 s-1 was estimated for the complexation of [NiIII(Me6-[14]aneN 4)H2O]3+ by D-mannitol. In addition, both carbohydrates accelerate the decay of the Ni(III) complex which occurs with half life t1/2 ? 102 ms. Consistent with the formation of fucoidan-Cu2+ complexes, the flash irradiations of these complexes at 351 nm produces transient spectra assigned to Cu+n (n = 2, 3) species. The non-linear dependence of the product concentration on the flash intensity shows that formation of the species is a biphotonic process. © 2011 Taylor & Francis.